Exenatide corrects postprandial hyperglycaemia in young people with cystic fibrosis and impaired glucose tolerance: A randomized crossover trial. Issue 3 (25th October 2018) - Geyer, Myfanwy C.; Sullivan, Thomas; Tai, Andrew; Morton, Judith M.; Edwards, Suzanne; Martin, A. James; Perano, Shiree J.; Gagliardi, Lucia; Rayner, Christopher K.; Horowitz, Michael; Couper, Jennifer J.
Abstract : Impaired glucose tolerance (IGT) in cystic fibrosis (CF) manifests as postprandial hyperglycaemia. Pancreatic enzyme supplementation reduces the latter; restoring incretin secretion and slowing gastric emptying. We aimed to determine the acute effect of exenatide on postprandial glycaemia in young people with CF and IGT. Six participants with CF and IGT were studied on 2 days, in a double‐blind randomized crossover trial. After overnight fasting, they received exenatide 2.5 mcg or placebo (0.9% saline) subcutaneously 15 minutes before a pancake meal labelled with 13 C octanoate and pancreatic enzyme replacement. The primary outcomes, area under the curve over 240 minutes (AUC 240 ) for blood glucose ( P < 0.0001) and peak blood glucose (7.65 mM ± 0.34 [mean ± SE] vs 9.53 mM ± 0.63, P < 0.0001), were markedly lower after exenatide than placebo. AUC240 for insulin, C‐peptide, glucagon‐like peptide‐1 (GLP‐1) and glucose‐dependent insulinotropic polypeptide (GIP) was also lower after exenatide. Gastric emptying was markedly slower after exenatide, as assessed by time for 10% gastric emptying and peak 13 CO2 excretion. We report for the first time that exenatide corrects postprandial hyperglycaemia in young people with CF and IGT. GLP‐1 agonists are a candidate treatment in CF‐related diabetes.